2016
DOI: 10.1016/j.ribaf.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Financial market interdependencies: A quantile regression analysis of volatility spillover

Abstract: This paper investigates the degree and structure of interdependence between emerging (Asian and Latin American) and developed (USA and Japan) stock markets through the study of volatility spillovers for the period spanning from January 1, 1993 to October 13, 2010. Using both standard GARCH model and quantile regression approach, we find the evidence of significant interdependence between financial markets which may give evidence of volatility transmission existence. The volatility transmission is closely assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 69 publications
3
32
0
1
Order By: Relevance
“…This fact indicated that the effects of shocks and lagged volatility persistence resulting from the market itself presented greater magnitude than those resulting from other markets, whether for the Latin American markets, or for the developed ones. This ascertainment is in accordance to what was detected by Rejeb & Arfaoui (2016).…”
Section: Interdependence Phenomenon and Asymmetriessupporting
confidence: 92%
See 1 more Smart Citation
“…This fact indicated that the effects of shocks and lagged volatility persistence resulting from the market itself presented greater magnitude than those resulting from other markets, whether for the Latin American markets, or for the developed ones. This ascertainment is in accordance to what was detected by Rejeb & Arfaoui (2016).…”
Section: Interdependence Phenomenon and Asymmetriessupporting
confidence: 92%
“…Several empirical studies also found similar results, such as those by Rejeb & Arfaoui (2016) and Valenzuela & Rodríguez (2015). The reason is that, for all the index pairs, a shock occurred in the t-1 returns of a market tends to increase the volatility of another one in t. Moreover, the conditional volatility of a certain index depends on past conditional volatilities of others.…”
Section: Interdependence Phenomenon and Asymmetriessupporting
confidence: 70%
“…On the one hand, by running the model in a long span of time, 1993-2013, we are able to test the decoupling hypothesis, measuring the evolution of volatility transmission and conditional correlation between US and Mexico and Brazil, the two largest markets in the region. On the other hand, to our knowledge, this is the first study that tests volatility transmissions between US and Latin American stock markets using the MGARCH-BEKK model, unlike previous studies (Christofi and Pericli, 1999;Edwards and Susmel, 2001;Weber, 2012;Rejeb and Arfaoui, 2015). The MGARCH-BEKK model is currently deemed as the standard methodology for detecting volatility spillovers amongst financial markets (Gannon and Au-Yeung 2004;Caporale, Pittis and Spagnolo, 2006;Koulakiotis, Dasilas and Papasyriopoulos, 2009;Hammoudeh, Yuan, McAleer and Thompson, 2010;Fayyad and Daly, 2011;Arouri, Jouini and Nguyen, 2011;Andreou, Matsi, and Savvides, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…A wide set of studies have explored volatility transmission between stock markets. For example, Lin, Engle and Ito (1994) Rejeb and Arfaoui, (2015), who study interdependence between the stock markets of US and Japan and a set of emerging stock markets, including five of Latin America, interpreting their results as an indirect evidence of volatility transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these indices, we have considered the volatility of oil prices and the volatility of the EUSTOXX European market. In this paper, we have used a quantile regression method (Engle and Manganelli, 2004;Alexander, 2008;Birău and Antonescu, 2014;Naifar, 2016;Aymen and Mongi, 2016) to analyze the impact of uncertainty on major European market indices. Precisely, we propose a new model based on quantitative regression approach to explore how the individual mentioned risk factors affect the returns and volatility of the market index DAX and the FTSE 100.…”
mentioning
confidence: 99%